2016
DOI: 10.1038/nature18315
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary research has consistently lower funding success

Abstract: Interdisciplinary research is widely considered a hothouse for innovation, and the only plausible approach to complex problems such as climate change. One barrier to interdisciplinary research is the widespread perception that interdisciplinary projects are less likely to be funded than those with a narrower focus. However, this commonly held belief has been difficult to evaluate objectively, partly because of lack of a comparable, quantitative measure of degree of interdisciplinarity that can be applied to fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
300
3
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 485 publications
(315 citation statements)
references
References 25 publications
3
300
3
9
Order By: Relevance
“…Known negative biases include those driven by gender (Pohlhaus 2011;Tricco et al 2017), race (Ginther et al 2011), institution size (Murray et al 2016), geographic location (Wahls 2016), and interdisciplinary study (Bromham et al 2016). Additionally, Boudreau et al (2016) found a tendency for reviewers with a shorter intellectual distance from an application to provide harsher evaluations even when they were highly innovative.…”
Section: The Process Is Biasedmentioning
confidence: 99%
“…Known negative biases include those driven by gender (Pohlhaus 2011;Tricco et al 2017), race (Ginther et al 2011), institution size (Murray et al 2016), geographic location (Wahls 2016), and interdisciplinary study (Bromham et al 2016). Additionally, Boudreau et al (2016) found a tendency for reviewers with a shorter intellectual distance from an application to provide harsher evaluations even when they were highly innovative.…”
Section: The Process Is Biasedmentioning
confidence: 99%
“…But we also know that funding interdisciplinary research presents challenges. There have been a number of initiatives over time at national and global levels to focus on this, as well as attempts to analyse what we really mean by interdisciplinary research (Bromham et al 2016). A greater focus on impact will mean these sorts of dynamics which relate to the value given to different types of research will need to be addressed head on.…”
Section: Implications For the Sector Of Assessing Research Impactmentioning
confidence: 99%
“…There are long-standing issues with inadequate assessment mechanisms for tenure and promotion (National Academy of Sciences, National Academy of Engineering & Institute of Medicine, 2005; British Academy Working Group on Interdisciplinarity, 2016; Klein and Falk-Krzesinski, 2017) and lower levels of success in grant applications (Bromham et al, 2016;Reckling and Fischer, 2010). This prompts two key questions:…”
Section: Introductionmentioning
confidence: 99%